Effects of Using Misoprostol for Cervical Ripening in Molar Pregnancy: A Double-blinded, Randomized Controlled Trial Study - Mirzamoradi, Masoumeh; Ashrafganjoei, Tahereh; Heidar, Zahra; Parsa, Tina; Bakhtiyari, Mahmood; Parsa, Yekta (Novelty in Biomedicine, 2026)
Background: Molar pregnancy is a rare and benign disease. If a molar pregnancy is diagnosed, treatment should be given immediately. Misoprostol is a synthetic prostaglandin analog commonly used for cervical ripening. This study was performed to determine the effects of misoprostol on cervical ripening in molar pregnancy. Materials and Methods: This double-blind, randomized clinical trial was performed on 150 pregnant women candidates for the termination of a molar pregnancy. Patients were divided into two intervention groups, receiving vaginal misoprostol at a dose of 400 μg four hours before suction-curettage, and the control group, treated by suction-curettage and using a vaginal placebo. Information, including age, education, history of abortion, curettage, molar pregnancy, time of last menstruation, gestational age, and consequences of misoprostol use, and bleeding during and after curettage, was included in a questionnaire. Data were analyzed using Stata ver 13MP using descriptive statistics, t-tests, chi-square tests, and Bonferroni post hoc tests. A P value < 0.05 was considered significant. Results: The study included 150 patients with an average age of 28 years. There was a significant association between the misoprostol group as an intervention and variables including age (p=0.003), gravidity (p<0.001), parity (p=0.011), delivery type (p=0.021), dilators (p<0.001), duration of surgery (p<0.001), and decreases in hemoglobin after curettage (p<0.001). Conclusion: Our study indicated that vaginal administration of misoprostol was a simple and effective treatment for terminating molar pregnancy and seemed to have significant advantages over the current methods.